Four Islands EcoHealth Network: an Australasian initiative building synergies between the restoration of ecosystems and human health. Issue 4 (10th May 2021) - Bradby, Keith; Wallace, Kiri J.; Cross, Adam T.; Flies, Emily J.; Witehira, Celia; Keesing, Amanda; Dudley, Todd; Breed, Martin F.; Howling, Gary; Weinstein, Philip; Aronson, James
Abstract : Reversing the spiraling trajectory of ecological degradation requires a profound paradigm shift that more explicitly links human and ecosystem health. Human health, as used here, includes well‐being and livelihoods, which are largely determined by socio‐cultural, economic, and environmental drivers. Ecological restoration and related restorative activities can contribute substantially to human health. However, restoration projects differ widely and health impacts can be difficult to quantify. Interdisciplinary restoration networks are important for investigating the complex socio‐cultural, economic, and environmental dynamics that characterize restoration practice and related health outcomes. We present the Four Islands EcoHealth Network (FIEN) as an exemplar for establishing interdisciplinary project connectivity to clarify intersections between ecosystem restoration and human health. FIEN is a cooperative regional restoration network within Australia and Aotearoa New Zealand which aims to research and devise strategies for restoration to simultaneously improve human health and repair native ecosystems. FIEN will operate collaboratively at local and regional scales to expand interdisciplinary research and outreach by linking research with experience‐based and Traditional Ecological Knowledge‐based restoration activities. The group's primary focus is value‐adding to the efforts of its constituent organizations by sharing expertise and methodologies to enable large‐scale analysis and comparison across adjacent regions, ultimately disseminating collective results through impactful science communication. We consider explicitly linking human and ecosystem health the best way forward to reverse the current downward trajectory of ecological degradation and declining human health, and propose FIEN as an approach which other restoration‐minded groups and coalitions might follow.